THU0554 Final Analysis of Study of Efficacy and Safety of Canakinumab in Active Hyper-IGD Syndrome. (9th June 2015) - Arόstegui, J.I.; Anton, J.; Calvo, I.; Robles, A.; Speziale, A.; Joubert, Y.; Junge, G.; Yagüe, J.
Abstract : Background: Hyper-IgD with periodic fever syndrome (HIDS) is a recessively inherited disorder characterized by periodic episodes of high fever, abdominal distress, joint pain, and skin rashes. Currently, no first line therapy exist to treat HIDS patients, with previous reports have shown heterogeneous outcomes. 1, 2 IL-1 blockade was reported efficient to reduce the frequency of inflammatory attacks and to improve clinical symptoms. 3 We herein report the final results of the study assessing the efficacy and safety of the anti-IL-1β human monoclonal antibody, canakinumab (CAN), in patients with active HIDS. Objectives: The primary objective was to assess the reduction of the frequency of flares during the 6-month treatment period compared to a historical treatment-free period. Secondary objectives included assessment of the reduction in the frequency of flares during the 24-month long-term follow-up and an assessment of adverse events (AE) reported during the trial. Methods: This was an open-label, single treatment arm, efficacy and safety study of SC CAN in patients with active HIDS older than two years. The study duration included a 6-month treatment period with up to 6-month treatment withdrawal period and 24-month long-term treatment period. Results: All patients (N=9) enrolled in the study completed the 6-month treatment and the 6-month withdrawal periods with 8 completing the 24-month long-term follow-up. The median number of flares decreased from 5 (3-12) during the historical period to 0 (0-2) during the treatment period. The median remained at 0 (0-3) until the end of the trial. During the long-term period, the median flare duration was 3.5 days (2-8) during the first 12 months and 8.5 days (6-11) during the second year. Flare severity remained "mild" to "moderate" at baseline and decreased to "mild" or "minimal" signs/symptoms and to "mild" or "without" signs/symptoms at the first and second year of the long-term period, respectively. PGA HIDS disease control scores changed in all patients from either "no control" or "poor control" at baseline, to "good" or "excellent control" by day 4 and were maintained at that level until the end of the study. CRP and SAA plasma levels normalized by day 15 and remained normal for the remainder of the study. The most frequent AEs were infections, consistent with that of previous CAN studies. Four patients experienced 14 SAEs (mild to moderate) and none were considered drug-related. Furthermore, there were no AEs leading to discontinuation of study treatment or study overall. Conclusions: Canakinumab markedly reduced the frequency of flares, rapidly alleviated signs and symptoms of acute episodes and normalized the serological inflammatory markers. No AEs lead to study or treatment discontinuation and the safety profile is consistent with other canakinumab studies. These data strongly support a safe and maintained disease control while patients were receiving treatment and reinforce the ongoing development of canakinumab in this therapeutic area. References: Drenth JP, et al. J Pharmacol Exp Ther 2001;298:1221-6. Picco P, et al. Ann Rheum Dis 2001;60:904. Bodar EJ, et al. Neth J Med 2005;63:260-4. Disclosure of Interest: J. I. Arόstegui Grant/research support from: Novartis, J. Anton Grant/research support from: Novartis, Consultant for: Novartis, Speakers bureau: Novartis, I. Calvo Grant/research support from: Pfizer, Abbvie, Novartis, Roche, Speakers bureau: Gebro, Pfizer, Abbvie, Novartis, A. Robles: None declared, A. Speziale Employee of: Novartis, Y. Joubert Employee of: Novartis, G. Junge Employee of: Novartis, J. Yagüe Grant/research support from: Novartis